Software Engineering International Summer Schools, LASER 2013-2014, Elba, Italy, Revised Tutorial Lectures - Meyer, Bertrand; Nordio, Martin (Programming and Software Engineering, 2015)
The LASER Summer School is intended for professionals from industry (engineers and managers) as well as university researchers, including PhD students. Participants learn about the most important software technology advances from pioneers in the field. Since its inception in 2004, the LASER Summer School has focused on an important software engineering topic each year. This volume contains selected lecture notes from the 10th LASER Summer School on Software Engineering: Leading-Edge Software Engineering. .